CANINE HYPERTROPHIC OSTEOPATHY: CASE REPORT - Borin, Sofía (2011)
A case of a 11 year old Boxer dog with hypertrophic osteopathy is presented. This isan uncommon pathological process characterized by bilaterally symmetric and generalizedperiosteal proliferative in long bones and falanges.